2016
DOI: 10.2196/resprot.4830
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Tailored Interventions to Enhance Prevention and Screening for Hepatitis C Virus Among People Who Inject Drugs: Protocol for a Randomized Pilot Study

Abstract: BackgroundHepatitis C virus (HCV) infection is a growing problem among people who inject drugs. Strategies to reduce disease transmission (eg, syringe exchange programs) and facilitate HCV screening and linkage are available but are under-utilized in many communities affected by injection drug use. Novel approaches to increasing the use of these strategies are needed.ObjectiveThe goals of this project are to (1) develop and pilot test a computerized tailored intervention for increasing HCV screening and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…As with primary HCV infection, a myriad of single and multicomponent prevention strategies have been suggested to reduce ongoing exposure [10]. These include provision of OAT and high-coverage needle-syringe programs (NSP) [34], as well as psychotherapy and peer-based drug cessation programs for stimulant use [35]. In our previous study, we have shown significant effect of OAT and psychotherapy in reducing risk of reinfection among PWIDs treated with interferon [20].…”
Section: Discussionmentioning
confidence: 99%
“…As with primary HCV infection, a myriad of single and multicomponent prevention strategies have been suggested to reduce ongoing exposure [10]. These include provision of OAT and high-coverage needle-syringe programs (NSP) [34], as well as psychotherapy and peer-based drug cessation programs for stimulant use [35]. In our previous study, we have shown significant effect of OAT and psychotherapy in reducing risk of reinfection among PWIDs treated with interferon [20].…”
Section: Discussionmentioning
confidence: 99%
“…Using the contact information provided at baseline, individuals were contacted 3 months later to complete the follow-up assessment. A protocol that describes in detail recruitment methods and intervention content and provides survey instruments and example content images of the Hep-Net intervention has been previously published [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recognizing the growing demand for targeted, evidence-based interventions and the existing infrastructure of SSPs, a computer-tailored risk reduction intervention, called Hep-Net, was developed and implemented through a pilot randomized controlled trial (RCT) [ 29 ]. The objectives of this study are to evaluate whether incorporating a computerized behavioral intervention into existing prevention services at SSPs can lead to the adoption of healthier behaviors, including safer injection practices, substance use reduction, overdose prevention, and HCV testing.…”
Section: Introductionmentioning
confidence: 99%
“…(Westergaard et al, 2016) Hep-Net was implemented in a community-based SEP that delivers prevention and testing services across Wisconsin through 10 statewide fixed sites as well as a mobile program. SEP staff enrolled 235 adults reporting past-month injection drug use into Hep-Net, and delivered a 2 session, computerized behavioral intervention aimed at promoting safer injecting behavior, linkage to addiction treatment, and HIV/HCV testing.…”
Section: Methodsmentioning
confidence: 99%
“…These programs often have established rapport and have earned the trust of target populations based on years of providing non-judgmental services. (Westergaard et al, 2016) Rapid screening for HCV is feasible and acceptable in SEPs (Barocas et al, 2014), and program staff is often knowledgeable and experienced in referring clients to other needed services. These features provide an opportunity to interface with difficult-to-reach populations that are both under-served and under-studied.…”
Section: Introductionmentioning
confidence: 99%